Aplikasi M-Learning Pada Dongle Melalui Nilai-Nilai Islam - Alfitriani Siregar; Imelda Darmayanti Manurung (UMSU, 2021)
This purpose of study analyzed mobile learning application using by Dangle tool through Islamic values for students of English department at Faculty of Teacher Training and Education in University of Muhammadiyah Sumatera Utara. Research method conducted descriptive qualitative. Population conducted of 136 students 4th semester of English department in 2019/2020 academic year in University of Muhammadiyah Sumatera Utara. Sample of 32 students taken Curriculum Design Material subject of English department at Faculty of Teacher Training and Education. The technique of collecting data used observation and documentation during the learning process. Data collection method carried out using by the spiral model of Kemmis and Mc and Taggart, these were; Action planning, treatment / observation of action, reflection and revision. The results of study showed the students can use the dongle properly and enthusiastically used it in the class of assignment presentation. M-learning application of dongle tool should be carried out in all classes in University of Muhammadiyah Sumatera Utara to advance learning technology.